Pengaruh kinerja keuangan terhadap nilai perusahaan pada industri infrastruktur telekomunikasi tahun 2017-2021 - Fajri, Ahmad; Munandar, Agus (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study is to examine and analyze the effect of financial performance, namely the current ratio, Debt to Equity Ratio, return on assets and return on equity on firm value (Price to Book Value). Investors certainly want developments in every business. Firm value is an indicator of financial performance that can be used by investors to assess the company's business development. The object of this research is the company in the Telecommunication Infrastructure Industry which is listed on the Indonesia Stock Exchange for the period 2017-2021. This study conducted a quantitative data analysis. The population of this study is the entire Telecommunication Infrastructure Industry listed on the Indonesia Stock Exchange 2017-2021. The sample used is 11 companies using purposive sampling as a sampling method. Data were analyzed using classical assumption test and multiple linear regression. This study proves that financial performance represented by the return on assets and return on equity has a positive and significant effect on firm value, while current ratio & Debt to Equity Ratio have no effect on firm value, respectively.